2022
DOI: 10.2147/ppa.s363082
|View full text |Cite
|
Sign up to set email alerts
|

Medication Adherence Among Geriatric Patients with Chronic Diseases in Riyadh, Saudi Arabia

Abstract: Background: Medication non-adherence is a common and significant public health problem, especially among the geriatric population. This study's objective was to measure medication adherence and associated factors among geriatric patients with chronic diseases. Methods: A cross-sectional study targeted outpatient geriatrics who suffer from chronic diseases at King Saud University Medical City (KSUMC), Riyadh, Saudi Arabia. Telephone interviews were utilized to collect data from participants using a structured q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…65 A study conducted in Saudi Arabia found a strong link between the degree of adherence and family assistance with medicine administration. 66 Family support is helpful for both drug adherence and treatment. 67 Stronger levels of social support and improved patient–physician relationships were associated with stronger medication adherence.…”
Section: Discussionmentioning
confidence: 99%
“…65 A study conducted in Saudi Arabia found a strong link between the degree of adherence and family assistance with medicine administration. 66 Family support is helpful for both drug adherence and treatment. 67 Stronger levels of social support and improved patient–physician relationships were associated with stronger medication adherence.…”
Section: Discussionmentioning
confidence: 99%
“…In the chronic disease population, our study found that the mean of the number of reasons for referral to counselling was significantly higher than the corresponding number in the non-chronic population (2.97 ± 1.56 vs. 1.45 ± 1.07). It is recognised that patients with chronic diseases are at high risk of multiple morbidity, which leads to high prevalence of polypharmacy and non-adherence ( Alhabib et al, 2022 , Aljawadi et al, 2022 ). In line with the above, chronic disease patients in our study showed a statistically significant greater frequency with respect to reasons for referral to counselling in all the counselling reasons addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Education and counselling about medication are essential among elderly patients who experience chronic diseases ( Marcum et al, 2013 , Chew et al, 2021 , Alhabib et al, 2022 ). Chronic disease conditions in the elderly lead to increased use of multiple medications and medication non-adherence ( Alhabib et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations